2007
DOI: 10.1590/s0004-282x2007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Non-choreic movement disorders as initial manifestations of Huntington's disease

Abstract: Huntington's disease (HD) is an autosomal dominantly inherited, progressive, neurodegenerative disorder characterized by cognitive decline, psychiatric disturbances, and involuntary movements -classically choreic. Symptoms usually present with slow progression leading to dementia and death approximately 15-20 years after disease onset 1 . Symptoms begin insidiously, most commonly between the ages of 35 and 50 years, with substantial variation that depends, in part, on the CAG repeat expansion length 1 . Chore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
1
12
1
2
Order By: Relevance
“…Our patients showed no response to levodopa, similar to observations reported for the hypokinesia seen in more advanced cases of HD [6]. In line with a previous report [7], we noted the presence of dystonia and myoclonus, both of which can be seen in HD, in some family members with HDL2 [8]. Progressive weight loss, which was an early sign in the original family with HDL2 [1], occurred throughout the disease course in our kindred, and is a common feature of HD.…”
Section: Discussionsupporting
confidence: 91%
“…Our patients showed no response to levodopa, similar to observations reported for the hypokinesia seen in more advanced cases of HD [6]. In line with a previous report [7], we noted the presence of dystonia and myoclonus, both of which can be seen in HD, in some family members with HDL2 [8]. Progressive weight loss, which was an early sign in the original family with HDL2 [1], occurred throughout the disease course in our kindred, and is a common feature of HD.…”
Section: Discussionsupporting
confidence: 91%
“…Juvenile HD, which is usually associated with expansions containing 60 or more CAG triplet repeats, often presents with dystonia or epilepsy (21). Patients who develop atypical movements during the course of the disease are also likely to harbor long expansions (12). However, in Squitieri's study (4), no difference was found in the average CAG numbers between patients with atypical onset motor symptoms and patients with typical ones.…”
Section: Discussionmentioning
confidence: 97%
“…Some adult-onset HD patients have atypical onset symptoms instead of chorea, behavioral of psychiatric disorders, and progressive dementia. Two western studies summarized the nonspecific onset movement including abnormalities of Parkinsonism, dystonia, ataxia, and tics[ 6 7 ] [ Table 1 ]. In Chinese adult-onset HD patients, atypical initial symptom of ataxia was reported.…”
Section: Linical C Haracteristicsmentioning
confidence: 99%